‘As deadly as armed conflict? Gang violence and forced displacement in the Northern Triangle of Central America’ - Cantor, David James (2016)
The flurry of interest around the European refugee crisis, whilst plainly justified, should not have the effect of distracting international attention from equally pressing humanitarian and refugee crises in other parts of the world. As such, this article highlights the extreme nature and scale of gang violence in the Northern Triangle countries of Central America, which has resulted in substantial forced displacement of affected populations. The article argues that, despite certain commonalities with situations of internal armed conflict (such as Syria), the scenario in the Northern Triangle poses a distinct set of additional challenges for ensuring the protection of refugees and displaced persons from these countries. The urgent need to address these challenges in the Americas is no less than for those presented by the current refugee crisis in Europe.